HUBUNGAN KUALITAS TIDUR DAN KEJADIAN SINDROM METABOLIK PADA LANSIA DI PUSKESMAS LUBUK BUAYA PADANG - Farah Novita Marjanah; Birman, Yuliza; Rifkind Malik (Yayasan Nusantara Hasana Berdikari, 2025)
Metabolic syndrome is a group of metabolic symptoms including high blood pressure, high blood sugar, cholesterol and obesity that can cause decreased organ system function. The high prevalence of metabolic syndrome is often found in the elderly group, which is 40%. Poor sleep quality is often found in the elderly group. Sleep quality and metabolic syndrome are related. To determine the relationship between sleep quality and the incidence of metabolic syndrome in the elderly at the Lubuk Buaya Padang Health Center. The study was conducted from December 2023 to January 2024 with the type of research being observational analytic. A total of 68 samples were used using consecutive sampling techniques. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using the chi-square test, data processing using computerized SPSS IBM version 25.0. The incidence of metabolic syndrome was experienced by 49 people (72.1%). The majority of the study samples had poor sleep quality, which was 55 people (80.9%). The study found a relationship between sleep quality and the incidence of metabolic syndrome at the Lubuk Buaya Padang Health Center (p = 0.005). There is a relationship between sleep quality and the incidence of metabolic syndrome at the Lubuk Buaya Padang Health Center.